2015
DOI: 10.1002/mdc3.12241
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation in a Case of Mitochondrial Disease

Abstract: Background DBS has proven to be an effective therapy for Parkinson's disease, essential tremor, and primary dystonia. Mixed results have been reported in case series for other hyperkinetic disorders, and sparse data are available regarding secondary movement disorders. We report on the clinical effects of bilateral globus pallidus internus (GPi) DBS, a progressive mitochondrial cytopathy. Methods A single patient with myoclonus and dystonia syndrome secondary to a mitochondrial cytopathy with history of perina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…An immediate therapeutic effect was found with DBS treatment of a patient with mitochondrial encephalopathy which remained stable for three years [199] . Martinez-Ramirez et al (2016) reported a case of DBS treatment on a patient with a biopsy proven complex I deficiency suffering from myoclonus and dystonia [200] . The effect of the DBS treatment was immediate, with symptoms being improved six months after DBS, however, a regression was observed 12 months post-DBS.…”
Section: Deep Brain Stimulation Strategies On Mitochondrial Disordersmentioning
confidence: 99%
“…An immediate therapeutic effect was found with DBS treatment of a patient with mitochondrial encephalopathy which remained stable for three years [199] . Martinez-Ramirez et al (2016) reported a case of DBS treatment on a patient with a biopsy proven complex I deficiency suffering from myoclonus and dystonia [200] . The effect of the DBS treatment was immediate, with symptoms being improved six months after DBS, however, a regression was observed 12 months post-DBS.…”
Section: Deep Brain Stimulation Strategies On Mitochondrial Disordersmentioning
confidence: 99%
“…Although there are no current reports of neuromodulatory intervention in children with MEPAN syndrome, the efficacy of GPi-DBS has been reported for movement disorders in other degenerative neurometabolic conditions such as PKAN and mitochondrial disorders (19,26,(46)(47)(48). GPi-DBS showed moderate efficacy in atypical PKAN, variable benefits in typical PKAN (19), and mixed effects in mitochondrial disease (26,(46)(47)(48). However, GPi-DBS may be less effective in cases of dystonia that present with structural abnormalities and will not affect the progression of the underlying metabolic condition.…”
Section: Discussionmentioning
confidence: 99%
“… 16 The optimal stimulation target, specifically with regard to mitochondrial disorders, has yet to be elucidated. 26 Typical targeting techniques are awake with MERs or asleep without MERs but with anatomical targeting. In our patient, her young age and high anxiety prevented us from performing awake surgery.…”
Section: Discussionmentioning
confidence: 99%